Minimalist G-modelling: A comment on Efron - Roger Koenker; Jiaying Gu (Centre for Microdata Methods and Practice (cemmap), 2019)
Efron's elegant approach to g-modeling for empirical Bayes problems is contrasted with an implementation of the Kiefer-Wolfowitz nonparametric maximum likelihood estimator for mixture models for several examples. The latter approach has the advantage that it is free of tuning parameters and consequently provides a relatively simple complementary method.
Keywords: 330; Nonparametric maximum likelihood; mixture model; convex optimization